Enantioselective arylation and vinylation of allylic bromides catalyzed by guanidinium and copper(I) salt - Jiang, Huan (2018)
The work during my Ph.D period was devoted to develop the asymmetric cross coupling reactions in the presence of chiral guanidinium catalyst. A series of guanidine-derived organocatalysis was developed in Prof Tan Choon Hong’s lab, showing great efficiency in asymmetric transformations. The thesis presented here is divided into three chapters, mainly discussing the exploration of enantioselective Csp3-Csp2 cross coupling to give optically active products in the presence of metal complex and chiral guanidinium catalyst. Chapter 1 of this thesis introduces the development of methodology for asymmetric Csp3-Csp2 cross coupling catalyzed by transition metals, assorted by types of electrophiles and nucleophiles employed in the reactions. Different transition metal complexes and ligands are discussed and compared in terms of capacity and disadvantage in asymmetric Csp3-Csp2 cross coupling. Proposal and objectives are raised at the end of Chapter 1 to address the possibility of using copper(I) salt and guanidinium for the reaction. The following part in Chapter 2 is the detailed investigation of asymmetric Csp3-Csp2 cross coupling catalyzed by copper(I) complex and guanidinium catalyst. An array of cyclic allylic bromides were transformed to corresponding arylated or vinylated products in good yields and high enantioselectivity. Mechanistic exploration of the cross coupling process involves: (1) X-Ray crystal structure and reactivity of guanidinium cuprate complex; (2) 63Cu NMR spectrum to observe the interaction between copper(I) complex and other reagents; (3) “Hard” nucleophilic attack pathway determined by change in the stereoselectivity of asymmetric allylic arylation process. Chapter 3 describes the extension of the developed methodology from cyclic bromides to various prochiral acyclic bromides, giving a wider substrate scope of SN2’ products in good enantioselectivity. The results illustrate the practicality of our catalyst system in asymmetric allylic substitution with various substrates.